Developing Critical Thinking Skills in Islamic Education: Pedagogical Approaches and Teacher Perspectives - Amina Van Der Linden; Khalid De Smet; Sofiane Dupuis (World Journal of Islamic Learning and Teaching, 2024)
The development of critical thinking skills in Islamic education is becoming increasingly important in this modern era, where students are expected to be able to analyze, evaluate and create new knowledge. This article explores pedagogical approaches that can be applied to improve critical thinking skills in Islamic education classrooms as well as teachers' perspectives regarding their implementation. Through literature studies and interviews with educators, this research identified a variety of strategies, including problem-based discussions, text analysis, and use of technology. The findings show that developing an interactive and participatory learning environment can help students develop better critical thinking skills. This article emphasizes the importance of training for teachers to support the implementation of these strategies in the context of Islamic education.